Differentially expressed genes linked to natural variation in long-term memory formation in Cotesia parasitic wasps - van Vugt, Joke J. F. A.; Hoedjes, Katja M.; van de Geest, Henri C.; Schijlen, Elio W. G. M.; Vet, Louise E. M.; Smid, Hans M. (Frontiers in Behavioral Neuroscience, 2015)
Even though learning and memory are universal traits in the Animal Kingdom, closely related species reveal substantial variation in learning rate and memory dynamics. To determine the genetic background of this natural variation, we studied two congeneric parasitic wasp species, Cotesia glomerata and C. rubecula, which lay their eggs in caterpillars of the large and small cabbage white butterfly. A successful egg laying event serves as an unconditioned stimulus in a classical conditioning paradigm, where plant odors become associated to the encounter of a suitable host caterpillar. Depending on the host species, the number of conditioning trials and the parasitic wasp species, three different types of transcription-dependent long-term memory (LTM) and one type of transcription-independent, anesthesia-resistant memory (ARM) can be distinguished. To identify transcripts underlying these differences in memory formation, we isolated mRNA from parasitic wasp heads at three different time points between induction and consolidation of each of the four memory types, and for each sample three biological replicates, where after strand-specific paired-end 100 bp deep sequencing. Transcriptomes were assembled de novo and differential expression was determined for each memory type and time point after conditioning, compared to unconditioned wasps. Most differentially expressed (DE) genes and antisense transcripts were only DE in one of the LTM types. Among the DE genes that were DE in two or more LTM types, were many protein kinases and phosphatases, small GTPases, receptors and ion channels. Some genes were DE in opposing directions between any of the LTM memory types and ARM, suggesting that ARM in Cotesia requires the transcription of genes inhibiting LTM or vice versa. We discuss our findings in the context of neuronal functioning, including RNA splicing and transport, epigenetic regulation, neurotransmitter/peptide synthesis and antisense transcription. In conclusion, these brain transcriptomes provide candidate genes that may be involved in the observed natural variation in LTM in closely related Cotesia parasitic wasp species.